Factors of Consumptive Behavior of Female Students Shopping on Shopee E-Commerce (Study of Shopee E-Commerce on the Consumptive Behavior of Female Students from the Faculty of Economics and Business at USU) - Fadhilah, Amalia; Badaruddin, Badaruddin; Pujiati, Pujiati (Lafadz Jaya Publisher, 2024)
Purchasing online through e-commerce makes it easier for consumers to choose and buy the goods they want. Consumptive behavior is individual behavior that is influenced by sociological factors in their lives which is shown to consume excessively or wastefully and unplannedly on services and goods that are not needed.There are many variations of products offered on Shopee e-commerce, including beauty products, men's clothing, women's clothing, cellphones, computers and accessories, home equipment, electronics, food & drinks. Shopee e-commerce also comes with several facilities that make things easier for buyers. The purpose of this research is to determine the factors that USU Faculty of Economics and Business students shop at Shopee e-commerce. This research uses the theory of consumption society which was put forward by Jean Baudrillad. The method used is a descriptive qualitative approach. This technique determines informants in this research using purposive and snowball. This research uses the Interactive Analysis Model from Miles and Huberman. The results of this research cause consumer behavior among students at the Faculty of Economics and Business due to internal and external factors, facilities provided by Shopee e-commerce, the influence of campus friends and factors that support work.